Clinical trials controlled, an activity rising in the province of Villa Clara - Migdalia Rodríguez Rivas; Rayza Méndez Triana; Rayza Marrero Toledo; Migdacelys Arboláez Estrada (Acta Médica del Centro, 2016)
Introduction: the clinical essays are the most rigorous investigations in the sphere of health and they allow to evaluate the efficacy and the safety of medicines, teams and procedures. In Villa Clara they began in 1992 and since then the number of professionals involved has increased, the specialties, the evaluated products, etc. Method: a documentary review and an interview were realized to managers and professionals related to the activity to compile information. Results: there have been realized 73 clinical essays (predominated those realized with the Center of Molecular Immunology and those directed to the therapy of the cancer) and the locations of lung and of breast that have been the most favored. Discussion: the number of professionals, medical specialties and participant institutions were increased and the correspondance was appreciated between the picture of health of the province and the developed clinical investigations. Conclusions: Villa Clara has experienced an increasing development in the activity of clinical essays and has achieved an improving of the scientific activity directed to the improvement of the medical attention and the quality of life of the patients.